Collected stories - Kafka, Franz, 1883-1924.; Josipovici, Gabriel, 1940- (New York : Distributed by Random House, 1993)
A selection of stories published before and after the death of the Austrian author, whose works are characterized by their nightmarish, illogical quality.
Includes bibliographical references (p. xli).
Wilson's Fiction.
Adult
Keywords: Short stories; Short stories